Clinical features of patients with hepatic portal venous gas - Fujii, Manato (BMC Surg, 2020)
BACKGROUND: Hepatic portal venous gas (HPVG) is a rare clinical condition that is caused by a variety of underlying diseases. However, the factors that would permit accurate identification of bowel ischemia, requiring surgery, in patients with HPVG have not been fully investigated. METHODS: Thirty patients that had been diagnosed with HPVG using computed tomography between 2010 and 2019 were allocated to two groups on the basis of clinical and intraoperative findings: those with (Group 1; n = 12 [40%]) and without (Group 2; n = 18 [60%]) bowel ischemia. Eleven patients underwent emergency surgery, and bowel ischemia was identified in eight of these (73%). Four patients in Group 1 were diagnosed with bowel ischemia, but treated palliatively because of their general condition. We compared the characteristics and outcomes of Groups 1 and 2 and identified possible prognostic factors for bowel ischemia. RESULTS: At admission, patients in Group 1 more commonly showed the peritoneal irritation sign, had lower base excess, higher lactate, and higher C-reactive protein, and more frequently had comorbid intestinal pneumatosis. Of the eight bowel ischemia surgery patients, four (50%) died, mainly because of anastomotic leak following bowel resection and primary anastomosis (3/4, 75%). All except one patient in Group 2, who presented with aspiration pneumonia, responded better to treatment. CONCLUSIONS: Earlier identification and grading of bowel ischemia according to the findings at admission should benefit patients with HPVG by reducing the incidence of unnecessary surgery and increasing the use of safer procedures, such as prophylactic stoma placement.